A Facile Synthesis of Nitrogen‐Doped Porous Carbon Materials for High‐Performance Supercapacitors. Issue 9 (4th March 2019) - Yao, Lu; Chen, Da‐Ming; Yan, Song; Lin, Jing‐Jing; Liu, Ye‐Ping; Lian, Jun; Liu, Yue‐Ran; Lin, Hua‐Lin; Han, Sheng
Abstract: A simple way for N‐doped porous carbon materials (ANCs) was prepared in N2 atmosphere through the KOH‐assisted carbonization of commercial melamine foam (MF) attached glucose. Adding glucose and KOH activation process have great effects on improving the electrochemical properties of ANCs materials. Compared with other materials, the optimal ANCs‐800, which is obtained with a KOH/glucose/MF weight ratio of 5:20:1 at 800 °C, exhibits the best capacitance performance with the specific surface area (SSA) of 1481 m 2 g −1 and high nitrogen content of 3.7 at. %. It possesses prominent specific capacitance (387 F g −1 at 0.5 A g −1 ) and excellent cycling stability (98.6% retention after 10, 000 cycles). Furthermore, in the symmetric supercapacitor, the ANCs‐800 electrode material maintains high energy density (24.2 W h kg −1 at 701.07 W kg −1 ) and great cycling performance (96.3% after 10, 000 cycles). Accordingly, the facile synthetic approach and attractive electrochemical properties make ANCs‐800 a popular capacitor material. Abstract : The N‐doped porous carbon materials (ANCs) were prepared by one‐pot method using melamine foam as skeleton and nitrogen source and glucose as carbon source. These materials present good electrochemical performance, and ANCs‐800 possesses prominent specific capacitance (387 F g −1 at 0.5 A g −1 ) and excellent cycling stability (98.6% retention after 10, 000 cycles).